Rekayasa Sistem Tata Air Lokasi Transmigrasi Palingkau Asri Lahan Usaha Satu SP-2 Di Wilayah Kabupaten Kapuas Propinsi Kalimantan Tengah - Prihanika Prihanika (Media Ilmiah Teknik Sipil, 2019)
Agriculture land in the transmigration location of Palingkau Asri is one of the development locations for tidal land development in Kalimantan. In its development this location has been divided into three settlement areas (SP), one of them is the SP-2. The focus of this research is Lahan Usaha Satu at SP-2. There are already irrigation networks consisting of irrigation channels (a simple drainage system) in the form of primary pilot channels, primary auxiliary channels, and tertiary channels. The main problems of this location include the excess of water that occurs in rainy seasons and a water system that does not function properly. To overcome these problems research was carried out in the following steps. Firstly, primary and secondary data were taken. Secondly, the water system optimization was examined using a mathematical model that was solved by using the HEC-RAS software package. Lastly, the problem of the excess water (floods) was solved by determining a dike height for a period of 25 years and optimizing the water system with water management structures such as watergates. The results indicated that the existing water management system still can handle the excess of water although the tertiary channels were overflowed (channel of T2, T4, T6, T12) especially at T6, where the overflow reached a maximum value of 1.1 m. The simulation with HEC-RAS